2013
DOI: 10.1186/1475-9276-12-56
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity among Norwegian adolescents- a multilevel analysis of how place of residence is associated with health behaviour: the Young-HUNT study

Abstract: IntroductionThe purpose of this article is to investigate whether and to what degree participation in physical activity among adolescents is associated with area economic deprivation in the municipality where they live. In the study we took account of aggregated informal social capital at the municipality level and compositional effects due to spatial concentration of individual variables known to be associated with physical activity. These include informal social participation, participation in other cultural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
1
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 39 publications
1
1
1
3
Order By: Relevance
“…In our study both boys and girls that reported hard training had more than 1 SD higher BMD at the femoral sites, compared to those who were sedentary. A former Norwegian population-based study reported participation in sports outside school for 16-years-old youth to a mean of 3.72 (SD 2.37) hours a week [41]. Compared to these, our adolescents reported slightly higher physical activity levels (0.56 hours, CI [0.325-0.795]).…”
Section: Discussioncontrasting
confidence: 68%
“…In our study both boys and girls that reported hard training had more than 1 SD higher BMD at the femoral sites, compared to those who were sedentary. A former Norwegian population-based study reported participation in sports outside school for 16-years-old youth to a mean of 3.72 (SD 2.37) hours a week [41]. Compared to these, our adolescents reported slightly higher physical activity levels (0.56 hours, CI [0.325-0.795]).…”
Section: Discussioncontrasting
confidence: 68%
“…Rural neighborhoods had more Active Living PA compared with urban, and individual participant educational level had somewhat different results depending on the neighborhood education level. Our findings of an independent association of neighborhood on Active Living and Sports PA confirm those of other studies of neighborhood influences (Mujahid et al, 2007; Piro et al, 2006; Riva et al, 2009) with neighborhood accounting for 3.8% of the variance in Active Living PA scores, similar to other studies (Boone-Heinonen et al, 2011; Logstein et al, 2013). …”
Section: Discussionsupporting
confidence: 91%
“…Social connectedness was measured two ways: by asking participants the number of neighbors that they knew by name [42] or the degree to which they agree with the statement ‘people in this neighborhood can be trusted.’ [61] Measures within this dimension that were at the aggregate level included: ‘Other Children in the Neighborhood’ measured as the population density of children [17] and ‘Social Relations’ measured using individual responses to Sampson’s neighborhood social cohesion and social control scale aggregated to the tract-level [62] and as individual’s social participation in different activities (e.g. recreational activities involving other people, activities of other political organizations; dining out or shopping with others) aggregated with other individual’s in the same neighborhood or municipality [63, 64].…”
Section: Resultsmentioning
confidence: 99%